2022
DOI: 10.3389/fnut.2022.823573
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Biochemical Factors Contributing to Cognitive Decline and B Vitamins in Patients With Alzheimer's Disease

Abstract: BackgroundMalnutrition, metabolism stress, inflammation, peripheral organs dysfunction, and B vitamins deficiency significantly contribute to the progression and mortality of Alzheimer's disease (AD). However, it is unclear which blood biochemical indicators are most closely related to cognitive decline and B vitamins deficiency (thiamine, folate, vitamin B12) in patients with AD.MethodsThis was a cross-sectional study of 206 AD patients recruited from six hospitals in China. Thiamine diphosphate (TDP), the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Moreover, the lower levels of these proteins were associated with disease severity. Previous investigation revealed the association between the lower levels of total protein and albumin and cognitive impairment in AD patients, and these reduced protein levels were identified as independent risk factors for rapid cognitive decline ( 58 60 ). A phase 2b/3 trial suggested that plasma exchange with albumin replacement could slow cognitive and functional decline in AD patients ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lower levels of these proteins were associated with disease severity. Previous investigation revealed the association between the lower levels of total protein and albumin and cognitive impairment in AD patients, and these reduced protein levels were identified as independent risk factors for rapid cognitive decline ( 58 60 ). A phase 2b/3 trial suggested that plasma exchange with albumin replacement could slow cognitive and functional decline in AD patients ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found the evidence supporting the notion that malnutrition causes thiamine metabolism disorders, affecting the activity and expression of thiamine diphosphate-related enzymes, thus increasing vascular inflammation and impairment of glomerular and tubular structure. This may also be the one of the reasons for the low levels of these proteins in the peripheral blood of AD patients ( 58 ). Importantly, this study delved into the potential diagnostic ability of these proteins for AD, and for the first time revealed that total protein level < 68.60 g/L, albumin level < 41.90 g/L, and globulin level < 27.10 g/L contributed to distinguish AD from non-AD.…”
Section: Discussionmentioning
confidence: 99%
“…In a four-year follow-up study, vitamin B6 was found to be an important protective factor in maintaining cognitive function in old age, especially in folate and vitamin B12 de cient populations [33]. In a cross-sectional study of 206 Alzheimer's patients, thiamine or its analogs supplementation was found to improve cognitive function [34]. A Chinese study also showed that higher dietary intakes of ribo avin and folate in midlife were associated with a reduced risk of cognitive impairment in old age [35].…”
Section: Discussionmentioning
confidence: 99%
“…Current interest in vitamin B 12 as a risk factor for AD is based on its relationship as a cofactor in the Hcy metabolism (Morris et al, 2006). A crosssectional study of 206 patients with AD recruited from six hospitals in China (Qian et al, 2022) and Jakubowski et al's (2021) research both indicated a possible pathogenic role of vitamin B 12 in MCI. Dos Santos and Pardi (2020) also indicated in a case-control study that there is a decrease in the levels of vitamin B 12 in patients with AD compared to healthy groups with biochemical evaluations.…”
Section: Figurementioning
confidence: 99%